Adsorption of rare earth metals (Sr2+ and La3+) from aqueous solution by Mg-aminoclay–humic acid [MgAC–HA] complexes in batch mode. Issue 2 (24th December 2015) - Lee, Young-Chul; Rengaraj, Arunkumar; Ryu, Taegong; Lee, Hyun Uk; An, Ha-Rim; Lee, Kug-Seung; Lee, Go-Woon; Kim, Jun Yeong; Heo, Nam Su; Kim, Byoung-Gyu; Huh, Yun Suk
Abstract : The recoveries of Sr 2+ and La 3+ as rare earth metals (REMs) were studied using Mg-aminoclay–humic acid [MgAC–HA] complexes prepared by self-assembled precipitation, i.e., [HA] intercalation into layered [MgAC]. Abstract : The recoveries of Sr 2+ and La 3+ as rare earth metals (REMs) were studied using Mg-aminoclay–humic acid [MgAC–HA] complexes prepared by self-assembled precipitation due to electrostatic attraction between water-solubilized [MgAC] and water-soluble [HA], and were compared with the recoveries using [MgAC] and [HA]. The influences of pH and Sr 2+ and La 3+ concentrations in single and binary systems were evaluated. The adsorbents before/after adsorption of Sr 2+ and La 3+ were characterized by (1) scanning electron microscopy (SEM) micrographs, (2) Fourier transform infrared (FT-IR), X-ray photoelectron spectroscopy (XPS), and extended X-ray absorption fine structure (EXAFS) spectra, and by (3) powder X-ray diffraction (XRD) pattern analysis. After fitting Langmuir and Freundlich isotherms, the Langmuir model was found to present better matches than the Freundlich one: the maximum adsorption capacities of Sr 2+ and La 3+ were 0.12 mg g −1 and 4.76 mg g −1 in the binary system at room temperature, and the optimal recovery pH was ∼8.0. In practical seawater meanwhile, the recoveries of Sr 2+ and La 3+ by [MgAC–HA] complexes were the highest in the binary system. However, with further recycling runs, the recoveries of Sr 2+ and La 3+ were critically diminished due to disassembly in [MgAC–HA] complexes under acidic conditions. Thus, for the purposes of industrial application, we are currently pursuing the enhancement of recyclability for [MgAC–HA] complexes by their encapsulation or direct hydrogel formation.